Retinal microperfusion after renal denervation in treatment-resistant hypertensive patients - Ott, Christian; Harazny, Joanna M.; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Bladowski, Marek; Michelson, Georg; Uder, Michael; Schmieder, Roland (Clinical Research in Cardiology, 2015)
High pulsatile pressure and flow in the arteries causes microvascular damage, and hence increased cardio-, and cerebrovascular complications. With advanced stages of hypertensive disease, an exaggerated pulsatile retinal capillary flow (RCF) has been shown, but data about interventional effect are missing.Fifty-one patients with true treatment-resistant hypertension (TRH) underwent renal denervation (RDN) using the Symplicity Flex(TM) catheter and were followed for 12 months. RCF was assessed non-invasively using Scanning laser Doppler flowmetry (SLDF) before, 6 (6 M), and 12 (12 M) months after RDN. RCF was measured in systole and diastole and pulsed RCF (difference of RCF in systole minus diastole) was calculated. In addition, flicker light-induced vasodilation (representing vasodilatory capacity) was assessed.Systolic and diastolic office blood pressure (BP) as well as 24-h ABPM decreased significantly 6 M and 12 M after RDN, compared to baseline values (all p < 0.001). There was a significant reduction of pulsed RCF 6 M (231 ± 81 versus 208 ± 68 AU, p = 0.046) and 12 M (194 ± 72 AU, p = 0.001) after RDN, whereas the mean RCF was unchanged. Moreover, there was a significant increase of flicker light-induced vasodilation after RDN (p = 0.043).In hypertensive patients with TRH, we observed a decrease of pulsed RCF 6 M and 12 M after RDN and an increase of vasodilatory capacity, in parallel to decreases in BP and heart rate. The reduction of pulsed RCF after RDN implies a decrease of shear stress on the vascular wall by the pulsed blood flow. This and the increment of vasodilatory capacity suggest an improvement of retinal (and potentially cerebral) microcirculation.
EVALuna2:3762